Effect of xanthan gum on physicochemical and textural properties of gluten-free batter and bread - Encina-Zelada, Christian (2019)
The objective of this study was to evaluate the effect of xanthan gum (XG) on physicochemical, rheological and textural properties of gluten-free batter and bread. Batches of gluten-free bread used a base formulation of rice, corn and quinoa flour, and different levels of XG (1.5, 2.5 and 3.5%) and water content (WC; 90, 100 and 110%) in a full factorial design. Although in interaction with water, higher XG doses tended to produce batters of lower stickiness, work of adhesion, strength-cohesiveness; which, when baked, produced loaves of lower specific volume and baking loss; and bread crumb of lower Aw, pH, hardness, springiness, firmness, mean cell area, void fraction, mean cell aspect ratio, and higher firmness, consistency, cohesiveness, adhesiveness, chewiness, resilience, cell density, cell size uniformity and mean cell compactness (p<.OOl). Gluten-free loaves of good appearance in terms of high specific volume, low crumb hardness, high crumb springiness, and open grain visual texture were obtained in formulations with 110% WC and XG doses between 1.5- 2.5%.